2006
DOI: 10.1159/000097038
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 Allele Frequency and Age at Onset of Alzheimer’s Disease

Abstract: The age distribution of the Ε4 allelic form of the apolipoprotein E gene (APOE) was investigated in 630 patients with Alzheimer’s disease (AD) with onset age ranging from 35 to 90 years. Overall, mean age at onset in APOE Ε4 allele bearers was significantly later than that in nonbearers. However, when stratified into early onset AD (EOAD) and late onset (LOAD) groups, mean age at onset in EOAD cases bearing APOE Ε4 allele was later than that in those EOAD cases without Ε4 allele, whereas in LOAD mean age at on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 39 publications
6
39
0
3
Order By: Relevance
“…These results are consistent with previous reports suggesting that the ε4 allele was a definite biological risk factor for AD and may increase the risk of developing EOAD [43,44]. One recent study revealed that the frequency of ε4 homozygotes was highest in the group of AD with an age at onset of 60-69 years which may further support our result of a higher frequency of ε4 homozygote in the EOMCI group [45].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous reports suggesting that the ε4 allele was a definite biological risk factor for AD and may increase the risk of developing EOAD [43,44]. One recent study revealed that the frequency of ε4 homozygotes was highest in the group of AD with an age at onset of 60-69 years which may further support our result of a higher frequency of ε4 homozygote in the EOMCI group [45].…”
Section: Discussionsupporting
confidence: 93%
“…APOE4 has been associated with about 65–75% of sporadic AD, but may be attributable to up to 20% of all dementias [5,6,7]. Furthermore, in a 1997 meta-analysis, the presence of an E4 allele decreased age at onset and increased the risk of disease as a gene dose, especially in patients with a disease onset between 40 and 60 years [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies report a higher prevalence of the APOE-4 allele in VaD patients, patients with mixed AD and VaD, and in post-stroke dementia [12,28,59,60] . Other studies found no evident role of APOE-4 in the pathophysiology of VaD or dementia after stroke [42-44, 49, 61-63] , which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%